Understanding Elementary Classroom Teachers' Use of Movement Integration Resources - Webster, Collin A.; Starrett, Angie; Rehling, Jeffery; Chen, Brian; Beets, Michael W.; Weaver, R. Glenn (Frontiers in Education, 2020)
Movement integration (MI) – infusing physical activity (PA) into normal classroom time during school – is an evidence-based strategy to support elementary children's health and education. However, few elementary classroom teachers in the United States appear to be using MI resources. In order to understand teachers’ MI resource use, this study’s purpose was threefold: (a) to examine teachers’ perceptions about MI and MI resources, (b) to identify teachers’ latent class membership based on their perceptions, and (c) to determine the extent to which teachers’ MI preferences, demographics, background, and school context predict class membership. We recruited a national sample of participants (N = 420) who completed an electronic survey including six sections: perceived benefits of MI, perceived barriers to using MI resources, satisfaction with MI resources, perceived importance of different MI resource characteristics, MI resource preferences, and participant demographics, background, and school context. Data analysis consisted of descriptive analyses, exploratory factor analysis, confirmatory factor analysis, latent profile analysis, and multinomial regression analysis. Participants mostly agreed about the benefits of MI and were satisfied with the MI resources they were using but had varying perceptions about the presence of barriers to using MI resources. Participants rated the integration of an MI resource with the academic curriculum, the amount of time required for teacher training, the type of training materials provided, and the timing of the training as the most important characteristics they would consider before adopting a resource. Factor analyses supported single factor solutions for perceived benefits, perceived barriers, and satisfaction, and a three-factor solution for perceived importance of different MI resource characteristics (Curriculum Integration, Training Logistics, and Feasibility). Based on these factors, we identified five latent classes of teachers. Regression results showed that desirable latent class membership depended on certain MI preferences and demographic, background, and school context characteristics. Teacher educators and interventionists should consider teachers’ MI perceptions, the nature of MI trainings, teacher characteristics, and school context in efforts to increase teachers’ use of MI resources. Further research is needed to explore the intrinsic value of MI for teachers, given MI’s education- and public health-related benefits.